PEMANFAATAN EKSTRAK AMPAS TAHU SEBAGAI MEDIA Trichoderma brevicompactum DALAM MENEKAN Fusarium sp. DAN MENINGKATKAN PERKECAMBAHAN BENIH CABAI - Aldianto S. Amas; Rida Iswati; Nikmah Musa (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2026)
Chili peppers (Capsicum annuum L.) are a commodity with high economic value and a very high consumption rate in Indonesia. The high demand is not matched by the availability of production, because chili plants are susceptible to Fusarium sp. disease. Farmers control the disease using chemical pesticides, the use of which causes negative impacts such as land degradation, death of natural enemies, and environmental pollution. A more environmentally friendly control alternative is Trichoderma sp., which is able to suppress Fusarium sp. pathogens and has the potential to increase plant growth. In this study, tofu dregs extract was used as a propagation medium for T. brevicompactum. This study aimed to examine the potential of tofu dregs extract as a propagation medium for T. brevicompactum, assess the effectiveness of the formulation in inhibiting Fusarium sp. in vitro, and evaluate its effect on chili seed germination. The research activities were carried out experimentally from April–July 2025 at the Biological Agent Laboratory of BPTPH Gorontalo Province. Observed parameters included media characteristics, growth and sporulation of T. brevicompactum, inhibition against Fusarium sp., and the formulation's ability to increase chili seed germination. Data were analyzed descriptively for the physical properties of the media, using a t test for spore density, and ANOVA followed by a 5% BNJ test for seed growth parameters. The results showed that tofu dregs extract effectively supported the growth and sporulation of T. brevicompactum. The resulting formulation effectively inhibited Fusarium sp. in vitro and increased chili seed viability in in vivo tests, with germination values equivalent to fungicide treatment. Tofu dregs extract has the potential to be a propagation medium for T. brevicompactum and its application as a biopesticide to suppress Fusarium sp. disease and stimulate chili seed germination.